2011
DOI: 10.1002/j.2055-2335.2011.tb00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Potentially Inappropriate Medication Use in Elderly Hospitalised Patients

Abstract: Background:The Beers criteria are used to identify potentially inappropriate medications (PIMs) in the elderly. Few studies have examined the Beers criteria in elderly hospitalised patients in Australia. Aim: To identify the prevalence of PIM use in elderly patients admitted to an Australian hospital using the 2003 Beers criteria. Method: A prospective cross-sectional study of 100 elderly inpatients was undertaken using the Beers criteria to identify and compare PIM on admission and discharge. Logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Several studies have used modified versions of the Beers criteria to identify potentially inappropriate medicine (PIM) prescribing for older Australians (Table ) . The studies used different modifications of the criteria, and different study methods, so the data are not directly comparable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have used modified versions of the Beers criteria to identify potentially inappropriate medicine (PIM) prescribing for older Australians (Table ) . The studies used different modifications of the criteria, and different study methods, so the data are not directly comparable.…”
Section: Resultsmentioning
confidence: 99%
“…The Screening Tool of Older Person's Prescriptions (STOPP), published in 2008 as an alternative to the Beers criteria, has not been widely used in Australia . A study in hospitalised older people using these criteria identified that 60% of patients were exposed to one or more PIMs (Table ) . PIMs most frequently identified using the Beers and STOPP criteria included: benzodiazepines, tricyclic antidepressants, anticholinergics, non‐steroidal anti‐inflammatory drugs and amiodarone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because medicine availability and use in Australia is largely determined by the Australian Pharmaceutical Benefits Scheme37. Other Australian studies have found that some medicines listed as inappropriate by Beers may be appropriate for certain older people according to Australian practice;105 many medicines listed by Beers are not available in Australia; and that some medicines considered inappropriate in Australia are not listed by Beers 106. Disagreement between Beers and other criteria, such as the improving prescribing in the elderly tool, have been identified 109…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has indicated a high prevalence of PP reported to be 76% among Australian older patients admitted to an acute care hospital. 16 In terms of PIMs and DDIs at admission, the prevalence in Australian elderly patients for at least 1 PIM and 1 DDI is 39-60% [38][39][40] and 71% 41 , respectively. Other studies have revealed the prevalence of PIMs among older hospitalized patients with cognitive impairment ranging from 53% to 90%.…”
Section: Introductionmentioning
confidence: 99%